Intervensi Minuman Fermentasi Kombucha untuk Meningkatkan Imunitas Perempuan Menopause: Program Pengabdian Masyarakat sebagai Bagian dari Diplomasi Kesehatan Nirmiliter - Mia Kusmiati; Sovian Aritonang; Hari Imbrani; Megha Sakova; Alice Agatha Delfreeta Aritonang; Hosianna Stephany Aritonang; M. Haris Sudrajat (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This article examines the effectiveness of fermented kombucha drinks in enhancing the immunity of menopausal women through an evidence-based nutrition approach. Additionally, the study highlights how community-based kombucha production and consumption programs can be part of non-military health diplomacy, supporting community resilience, especially for vulnerable groups like menopausal women who experience immune function decline due to hormonal changes. Using the Systematic Literature Review (SLR) method, the study analyzes 30 relevant articles published between 2018–2025 from reputable sources such as Scopus, PubMed, and others. The findings show that (1) kombucha improves immunity through cytokine modulation and increased antioxidant activity, (2) kombucha normalizes gut microbiota, contributing to the immune health of menopausal women, (3) fermentation variations and microbial composition affect kombucha's effectiveness, and (4) community-based kombucha production programs have potential in enhancing health literacy and local economic empowerment. This study provides a basis for local governments, health centers, and communities to integrate kombucha as a preventive health intervention, while also strengthening community resilience through nutrition education and functional food entrepreneurship. The article also offers a new conceptual model, “Kombucha Intervention – Immunity – Health Diplomacy,” that connects biological evidence, community health, and non-military resilience integratively.